STAT6 polymorphisms are associated with neonatal regulatory T cells and cytokines and atopic diseases at 3 years. Issue 10 (21st September 2013) - Casaca, V. I.; Illi, S.; Klucker, E.; Ballenberger, N.; Schedel, M.; von, E.; Kabesch, M.; Schaub, B.
Abstract Background The transcription factor STAT6 is crucial for activation of the interleukin (IL)‐4/IL‐13 pathway and has been linked to regulatory T cells (Tregs). Associations of STAT6 polymorphisms with IgE levels were described; however, their impact on neonatal immune responses and early disease development is unknown. Methods STAT6 polymorphisms were genotyped in cord blood mononuclear cells by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF‐MS). Gene expression was assessed by real‐time polymerase chain reaction (PCR) and cytokines by Multiplex. At age 3 years, atopic diseases were assessed by questionnaires. Results STAT6 rs324011 but not rs1059513 polymorphism was associated with significant or borderline significant decreased mRNA expression of Treg‐associated genes (FOXP3, GITR, LAG3). Heterozygotes and minor allele homozygotes of rs324011 had low levels of tumor necrosis factor alpha (TNF‐α) and increased interferon gamma (IFN‐γ) (P ≤ 0.04), while heterozygotes and minor allele homozygotes of rs1059513 had increased TNF‐α and Granulocyte–macrophage colony‐stimulating factor (GM‐CSF) (P ≤ 0.05). In minor allele homozygotes of rs324011, expression of Treg‐associated genes was strongly inverse correlated with IFN‐γ (unstimulated, r = −0.7, P = 0.111; LpA stimulation, r = −0.8, P = 0.011), but not in heterozygotes or major allele homozygotes. Heterozygotes and minor allele homozygotes of rs324011 presented a lower risk of atopic dermatitis and obstructive bronchitis until age 3 years. Conclusions Two STAT6 polymorphisms were associated with altered immune responses already at birth. STAT6 rs324011 was associated with lower neonatal Treg and increased Th1 response. Those neonates had a lower risk of atopic dermatitis and obstructive bronchitis until 3 years. Our data suggest a role for STAT6 polymorphisms in early immune regulation and implications on early atopic disease development.